DBU‐Promoted Three‐Component Cascade Annulations to Access Multiply Substituted 3‐Cyano‐thiophenes. Issue 10 (8th September 2022) - Zheng, Lvyin; Liu, Gongping; Zou, Xiaoying; Zhong, Yumei; Deng, Lei; Wu, Yingying; Yang, Beining; Wang, Yihan; Guo, Wei
Abstract: Metal‐free [2+2+1] three‐component cascade annulations for the one‐pot synthesis of multiply substituted 3‐cyano‐thiophenes from 3‐oxo‐nitriles, enones and elemental sulfur are described. This DBU‐promoted protocol features good functional group tolerance, and provides high value 3‐cyano‐thiophenes in moderate to good yields under simple reaction conditions. This approach also enables late‐stage modifications of structurally complex bioactive molecules and drugs, which exhibits potential applications in medicinal chemistry. Abstract : Metal‐free [2+2+1] three‐component cascade annulations for the one‐pot synthesis of multiply substituted 3‐cyano‐thiophenes from 3‐oxo‐nitriles, enones and elemental sulfur are described. This DBU‐promoted protocol features good functional group tolerance and provides high value 3‐cyano‐thiophenes in moderate to good yields under simple reaction conditions.